2002
DOI: 10.1097/00004872-200211000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension magnitude and management in the elderly population of Spain

Abstract: Hypertension is a major public health problem in elderly Spaniards. Most hypertensives had their hypertension uncontrolled. Greater emphasis should be laid on the most disadvantaged (the older, men, and those with lowest education) in terms of hypertension management, and on reinforcing weight loss and combining drugs for enhanced hypertension control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
6
23

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(109 citation statements)
references
References 20 publications
11
69
6
23
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
“…It has been suggested that, in middle-aged and older people with high SBP, PP is a more important determinant of risk for coronary heart disease than SBP or DBP. 16,17 The independent association of short stature with increased PP suggests that PP could be a potential mediator of the relation between short stature and increased risk of coronary heart disease that has been seen in many studies. 4,19 This would also explain the paradox of the consistent findings about the relation between height and coronary heart disease and the inconsistent findings about the association of short stature with SBP and DBP.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplementioning
confidence: 99%
“…Ethical committee approval for the study was obtained and all subjects gave informed consent; full details of participants and measurements have been reported previously. 17,18 The information was collected by personal interview using a structured questionnaire, followed by a physical examination to measure anthropometric characteristics and blood pressure.…”
Section: Participantsmentioning
confidence: 99%
“…1,14,15,17,[19][20][21][22][23][24][25][26][27] Among hypertensives, those who responded in the negative to 'Have you ever been diagnosed with high blood pressure by a medical professional?' were considered to be unaware and those who responded in the negative to 'Are you presently taking any medicine prescribed by a physician for high blood pressure?'…”
Section: Definitionsmentioning
confidence: 99%
“…4,6 Recognizing the elderly as an at-risk population, studies in various countries have documented the prevalence and correlates of hypertension and of awareness, treatment and control of hypertension among the elderly. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] These studies suggest considerable heterogeneity for the prevalence of these conditions across elderly subgroups, defined by socio-demographic or health characteristics. Furthermore, neither the prevalence nor the identified correlates are uniform across countries.…”
Section: Introductionmentioning
confidence: 99%